IMPLEMENTASI KEBIJAKAN TRANSAKSI NON TUNAI DALAM PENGELOLAAN KEUANGAN DAERAH DI KABUPATEN BANDUNG (Studi pada Sekretariat Daerah Kabupaten Bandung): Array - Yati Kurniati; Heru Nurasa; Candradewini (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
Good governance constantly updates every policy, one of which is the mandatory implementation of non-cash transactions. The Bandung Regency Government is one of the ones that started implementing a non-cash transaction system carried out in stages in early 2018 which includes revenue and expenditure transactions. Where the implementation is based on the Bandung Regent Regulation Number 22 of 2018 concerning the Implementation of Non-Cash Transactions in the Bandung Regency Government Environment. The purpose of this research is to study, analyze and understand in depth. This research uses qualitative research methods (Qualitative Research). In examining the implementation of non-cash transaction policies in regional financial management at the Regional Secretariat of Bandung Regency, the author uses the theory proposed by Grindle that two groups of main factors influence the success of policy implementation, namely: content of policy and policy context variables (context). of implementation). The Regional Secretariat of Bandung Regency in the Implementation of Non-Cash Transactions based on the Grindle perspective can run well in accordance with each variable